Foundational dendritic processing that is independent of the cell type-specific structure in model primary neurons. (16th November 2015) - Kim, Hojeong; Heckman, C.J.
Highlights: Primary neurons in CNS exhibit very distinctive structures of the dendrites. Dependency of dendritic signalling and excitability and their relationship on cell specific structure is investigated among different types of primary neurons. All anatomically reconstructed primary neurons show similar directional signalling, locational excitability and their relationship over the dendrites. This study identifies foundational features of dendritic processing shared across primary neurons. Abstract: It has long been known that primary neurons in the brain and spinal cord exhibit very distinctive dendritic structures. However, it remains unclear whether dendritic processing for signal propagation and channel activation over dendrites is a function of the cell type-specific dendritic structure. By applying an extended analysis of signal attenuation for the physiological distributions of synaptic inputs and active channels on dendritic branches, we first demonstrate that regardless of their specific structure, all anatomically reconstructed models of primary neurons display a similar pattern of directional signal attenuation and locational channel activation over their dendrites. Then, using a novel modeling approach that allows direct comparison of the anatomically reconstructed primary neurons with their reduced models that exclusively retain anatomical dendritic signaling without being associated with structural specificity, we show that the reduced model can accurately predict dendritic excitability of the anatomical model in both passive and active mode. These results indicate that the directional signaling, locational excitability and their relationship are foundational features of dendritic processing that are independent of the cell type-specific structure across primary neurons.